RETRACTED : Pengembangan tes penjelasan ilmiah materi sistem ekskresi manusia untuk siswa SMP/MTs kelas VIII - Isna Istikhanif Farida; Muntholib Muntholib; A. M. Setiawan (Universitas Negeri Malang, 2021)
Following a rigorous, carefully concerns and considered review of the article published in Jurnal MIPA dan Pembelajarannya (Journal of Mathematics, Science, and Instruction) to article entitle